La gestion terrestre d’une pollution d’origine maritime à l’échelle locale : quelle intégration ? - Vincent Herbert (VertigO)
With the local scale, stakeholders often perceive the risks of coastal pollution by hydrocarbons by a maritime entry, where the preventive solutions would emanate from international authorities. Nevertheless, in the scope of coastal management of pollution, it is advisable to integrate this risk in the management of coastal territories, as well as other risks (erosion, telluric pollution…). The aim of integrated coastal zone management is a better coordination of local management for an effective preparation of the terrestrial fight. Intercommunality scale seems to be the best way to ensure the interrelationship between the national and international scale and the communal level.